Phosphorylation in Novel Mitochondrial Creatine Kinase Tyrosine Residues Render Cardioprotection against Hypoxia/Reoxygenation Injury - Park, Nammi; Marquez, Jubert; Garcia, Maria Victoria Faith; Shimizu, Ippei; Lee, Sung Ryul; Kim, Hyoung Kyu; Han, Jin (Journal of Lipid and Atherosclerosis, 2021)
Ischemic cardiomyopathy (ICM) is the leading cause of heart failure. Proteomic and genomic studies have demonstrated ischemic preconditioning (IPC) can assert cardioprotection against ICM through mitochondrial function regulation. Considering IPC is conducted in a relatively brief period, regulation of protein expression also occurs very rapidly, highlighting the importance of protein function modulation by post-translational modifications. This study aimed to identify and analyze novel phosphorylated mitochondrial proteins that can be harnessed for therapeutic strategies for preventing ischemia/reperfusion (I/R) injury. Sprague-Dawley rat hearts were used in an Langendorff system to simulate normal perfusion, I/R, and IPC condition, after which the samples were prepared for phosphoproteomic analysis. Employing human cardiomyocyte AC16 cells, we investigated the cardioprotective role of CKMT2 through overexpression and how site-directed mutagenesis of putative CKMT2 phosphorylation sites (Y159A, Y255A, and Y368A) can affect cardioprotection by measuring CKMT2 protein activity, mitochondrial function and protein expression changes. The phosphoproteomic analysis revealed dephosphorylation of mitochondrial creatine kinase (CKMT2) during ischemia and I/R, while preserving its phosphorylated state during IPC. CKMT2 overexpression conferred cardioprotection against hypoxia/reoxygenation (H/R) by increasing cell viability and mitochondrial adenosine triphosphate level, preserving mitochondrial membrane potential, and reduced reactive oxygen species (ROS) generation, while phosphomutations, especially in Y368, nullified cardioprotection by significantly reducing cell viability and increasing ROS production during H/R. CKMT2 overexpression increased mitochondrial function by mediating the proliferator-activated receptor γ coactivator-1α/estrogen-related receptor-α pathway, and these effects were mostly inhibited by Y368A mutation. These results suggest that regulation of quantitative expression and phosphorylation site Y368 of CKMT2 offers a unique mechanism in future ICM therapeutics.